Desenvolvimento de uma versão portuguesa do nutritional risk screening NRS 2002 - Amaral, Teresa (2020)
The Nutritional Risk Screening (NRS 2002) is a tool that was developed by the Danish Society for Parenteral and Enteral Nutrition. It is a valid system that allows the detection of the risk of undernutrition or of undernutrition in hospitalized individuals and is applied by health professionals. A Portuguese language version of NRS 2002 was developed with linguistic and cultural equivalence to the original using the WHO proposed methodology "Process of translation and adaptation of instruments". Advanced translation and back-translation were carried out through the following steps: translation (1st stage), back-translation performed by one or more specialists (2nd stage), pre test (3rd stage) and preparation of the final version (4th stage). This article aims to describe this process and also the Portuguese version of NRS 2002.